Об энергии на долоте и ее реализации - Алексеев, Л.А.; Ишбаев, Г.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The report considers energetic aspects of rock destruction tool work from the point of view of its construction, properties of cutter material, and drilling regime. The ways of efficiency increasing of energy utilizing in cutting-shearing-tyre drillbits, prevention of catastrophic abrasion, and increasing the rate of penetration are shown.